A useful approach for making the correct diagnosis of mucosal melanoma. Issue 1 (1st January 2016) - Kamizono, Kenichi; Fujii, Satoshi; Katsura, Motoyasu; Hayashi, Ryuichi
Abstract: Oral macule and mucosal melanoma are often difficult to differentiate from each other, and a conclusive diagnosis of mucosal melanoma is difficult to make, either clinically or pathologically, in younger adults. We report the case of a 26-year-old female who presented with a black pigmented lesion of the left upper gingiva. The lesion was finally diagnosed as a mucosal melanoma 10 months after the patient's first visit to a hospital. She received partial left maxillectomy. She has been alive without active disease for 3 years after first operation. Considering that in general, subepithelial invasion is seen even from the early phase in cases of mucosal melanoma, prompt and precise pathological diagnosis is necessary to ensure appropriate therapy.